Forest Administration Reports - Smythies, E. A. (Indian Forester, 1939)
Forest Administration Reports are usually extremely dull reading, and filled with a mass of minor details and relatively unimportant matter. They would be more interesting to legislators, the general public, and to other provinces, if unimportant details were omitted, and greater attention paid to important matters of policy, and to trends of administration and developments.